Paciente masculino de 32 años de edad con hiperlipidemia - Peralta Guadamud, Jenniffer María (2019)
The present case study was base don a 32 year old male patient with hyperlipidemia is when too much lipid (fat) is found in the blood. These fats include cholesterol and triglycerides which are important for the functioning of the organism. When the level excedes this fat may present danger in the person such as heart disease or stroke. In order to modify the patient´s lifestyle by means of an appropriate diet. Anthropometric evaluation is performed where the patient is in a normal IMC, biochemical examination high cholesterol and triglycerides, values, clinical examination shows xantomatosis eruptive and evaluation excessive fat intake, so we proceed to carry out a diet hypographase, avoid risks of stroke and promote physical activity. Obesity, lack of exercise, a diet rich in saturated fat and few fruits, vegetables and fiber foods can contribute to hyperlipidemia. The diet is based on 2059kcal/day hipograse which will be divided intro 5 meals. With a caloric supply of carbohydrates 60% (308.7gr), proteins 15% (77.2gr), fat 25% (57.1gr).